2017
DOI: 10.1002/chem.201700572
|View full text |Cite
|
Sign up to set email alerts
|

Application of Thiol–yne/Thiol–ene Reactions for Peptide and Protein Macrocyclizations

Abstract: The application of thiol-yne/thiol-ene reactions to synthesize mono- and bicyclic-stapled peptides and proteins is reported. First, a thiol-ene-based peptide-stapling method in aqueous conditions was developed. This method enabled the efficient stapling of recombinantly expressed coil-coiled proteins. The resulting stapled protein demonstrated higher stability in its secondary structure than the unstapled version. Furthermore, a thiol-yne coupling was performed by using an α,ω-diyne to react with two cysteine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 33 publications
1
53
0
Order By: Relevance
“…RGD was intentionally used as model due to its broad use as a cancer cell-targeting peptide as well as its bulky Arg/Asp residues, which could be used to examine the reaction's chemoselectivity and functional group tolerance. 16 Based on our trials, this reaction could not be applied in solid phase synthesis. This may be due to the low nucleophilicity of the residue and its pseudo-dilution effect in solid phase, or the degradation of cyclized peptides in the resin cleavage cocktail (TFA/TIS/EDT/H 2 O).…”
Section: Resultsmentioning
confidence: 99%
“…RGD was intentionally used as model due to its broad use as a cancer cell-targeting peptide as well as its bulky Arg/Asp residues, which could be used to examine the reaction's chemoselectivity and functional group tolerance. 16 Based on our trials, this reaction could not be applied in solid phase synthesis. This may be due to the low nucleophilicity of the residue and its pseudo-dilution effect in solid phase, or the degradation of cyclized peptides in the resin cleavage cocktail (TFA/TIS/EDT/H 2 O).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the authors highlight the compatibility of this methodology with unprotected peptides without the requirement for unnatural amino acids. Further work by Wang et al on this methodology has adapted this stapling reaction for aqueous conditions (Wang et al, 2017) Figure 3B. This was achieved through use of the water-soluble VA044 radical initiator in combination with water-soluble diallylurea staples.…”
Section: Two-component Systemsmentioning
confidence: 99%
“…Molecular dynamics simulations suggested that the unconstrained peptides exhibited an extended helical conformation, while the single‐ and double‐thiol‐ene constrained peptides adopted a “collapsed” conformation. This atypical conformation was hypothesized to be the cause of more rapid degradation …”
Section: New Constraintsmentioning
confidence: 99%
“…Reacting an ⍺,ω‐diyne with two cysteines formed a divinyl sulfide linker which was reacted in a thiol‐ene reaction with a second peptide containing two cysteines to form a bicyclic constrained peptide (Figure B). This linker also allowed for other types of functionalization, including groups that enhance water solubility and cell permeability, as illustrated by Wang et al with the addition of a CRRRRC motif to the constrained peptide.…”
Section: Double‐stapled Bicyclic Peptidesmentioning
confidence: 99%